Spectral attenuation of global and diffuse UV irradiance and actinic flux by clouds. (29th March 2014) - Mateos, D.; di Sarra, A.; Bilbao, J.; Meloni, D.; Pace, G.; de Miguel, A.; Casasanta, G.
<x xml:space="preserve">Abstract</x> Measurements of spectral global and diffuse ultraviolet (UV) irradiance, and of spectral actinic flux were made jointly with determinations of cloud properties during a two‐ month experimental campaign that took place in southern Italy in May–June 2010. The cloud modification factor (CMF) which is the ratio between the incoming radiation under cloudy and in cloud‐free conditions, was obtained for the global (direct plus diffuse) and diffuse components of the irradiance, and for the actinic flux in the UV spectral range for overcast conditions. Measurements of the diffuse irradiance and actinic flux CMFs are very scarce, and are particularly important to characterize the radiation field and verify the behaviour of radiative transfer models in cloudy conditions. In addition to measurements, one‐dimensional radiative transfer simulations are used to investigate the cloud influence on the spectral solar UV radiation. The analysis shows that the wavelength dependence of CMF for the global irradiance is mainly due to the normalization for cloud‐free conditions. The CMF for the diffuse irradiance and for the actinic flux displays a strong dependence on the solar zenith angle. This dependence appears to be mainly driven by the large role played by the zenith radiation in overcast conditions. Radiative transfer model determinations of CMF satisfactorily reproduce observations.